2011
DOI: 10.1073/pnas.1012401108
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin-mediated dendrite-to-nucleus signaling revealed by microfluidic compartmentalization of dendrites

Abstract: Signaling from dendritic synapses to the nucleus regulates important aspects of neuronal function, including synaptic plasticity. The neurotrophin brain-derived neurotrophic factor (BDNF) can induce long-lasting strengthening of synapses in vivo and this effect is dependent on transcription. However, the mechanism of signaling to the nucleus is not well understood. Here we describe a microfluidic culture device to investigate dendrite-to-nucleus signaling. Using these microfluidic devices, we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
91
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 53 publications
(60 reference statements)
1
91
1
Order By: Relevance
“…Because BDNF-containing endosomes are likely to be biochemically active (12)(13)(14)(15), they could exert prolonged localized action of BDNF-TrkB signaling in the postsynaptic cytoplasm. Mobile endosomes could also spread BDNF-TrkB signals in the extrasynaptic region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because BDNF-containing endosomes are likely to be biochemically active (12)(13)(14)(15), they could exert prolonged localized action of BDNF-TrkB signaling in the postsynaptic cytoplasm. Mobile endosomes could also spread BDNF-TrkB signals in the extrasynaptic region.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophin binding to its receptor leads to cytoplasmic signaling as well as internalization of the neurotrophin-receptor complexes. These endocytosed neurotrophin-receptor complexes remain active in the form of "signaling endosomes" that could be transported over long distances within neuronal cytoplasm to exert its regulatory functions within the neuron (12)(13)(14)(15). In this study, we have examined the possibility that these endosomes may undergo activity-dependent exocytosis at postsynaptic dendrites, thus providing an additional source of synaptic BDNF.…”
mentioning
confidence: 99%
“…A recent study using a microfluidic device that allows the isolation of the dendritic compartment showed that BDNF acts on dendrites of cultured cortical neurons to induce an signal that upregulates the expression of the IEG Arc and c-Fos (Cohen et al, 2011) (Fig. 1).…”
Section: Bdnf-induced Changes In the Transcription Activity And The Smentioning
confidence: 99%
“…The effect of BDNF in the signaling from dendrites to the nucleus depends on MEK1/2 (MAPK and ERK kinase, type 1/ 2), and activity of the TrkB receptors to induce gene expression is required mainly in the soma compartment. However, distinct mechanisms are involved in the regulation of the expression of the two genes since the Ca 2þ concentration in the soma and in the dendritic compartments influenced the expression of Arc but not cFos (Cohen et al, 2011). Additional studies are required to identify other genes that are specifically regulated following activation of dendritic receptors for BDNF.…”
Section: Bdnf-induced Changes In the Transcription Activity And The Smentioning
confidence: 99%
“…It is involved in rapid local changes at the synapse and has a long-term effect on the transcription of genes that are important for neuronal plasticity, such as c-Fos and Arc (2,3). BDNF plays a critical role in activitydependent synaptic plasticity, particularly long-term potentiation (LTP) (3)(4)(5)(6).…”
mentioning
confidence: 99%